(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2021)
Formant transitions reflect the overall change in the shape of the vocal tract during speech production. The objective of the study was to analyze F1 and F2 transition in Macedonian vowels in consonant context. This study included 12 native speakers of Macedonian (mean age of 42.7±11.9 years). Vowel /o/ in dento-alveolar plosive context /do/ had falling F2 transition in the duration of 38 ms and transition extent 772 Hz, and in velar plosive context /ɡo/ had falling F2 transition in the duration of 25 ms and transition extent 85 Hz. Vowel /a/ in alveolar fricative context /ʃa/ had falling F2 transition in the duration of 25 ms and transition extent 324 Hz, and in labial fricative context /fa/ had rising F2 transition in the duration of 38 ms and transition extent 214 Hz. Vowel /u/ in palatal fricative context /ju/ had falling F2 transition in the duration of 48 ms and transition extent 1084 Hz. F2 locus for dento-alveolar consonant was 1900 Hz, for velar 2100 Hz, for alveolar 1700 Hz, for labial 1200 Hz, and for palatal consonant was 2600 Hz. F2 locus is the highest for palatal consonants and the lowest for labial consonants. F2 transition is an acoustic cue for the place of articulation.